Experimental Comparison of DALI and 0–10V LED Dimming Systems for Smart Lighting - MUHAMMAD RISQI NURYANA; MARSUL SIREGAR; KAREL OCTAVIANUS BACHRI (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
This study compares the dimming performance of DALI and 0–10 V using three commercial LED drivers at eight dimming levels. The testing included power consumption, illuminance, and flicker stability. The results showed that DALI was able to maintain a linear dimming curve down to low levels such as 10%, 5%, and 1%, with consistent flicker within the No Risk zone. Power consumption at 0% was also low, making it suitable for applications requiring deep dimming and stable visual comfort. Conversely, the 0–10 V system performed quite well at high levels and was slightly more efficient at low power, but its performance dropped drastically below 30%. At 10%, the illuminance was almost zero and the flicker level entered the High Risk zone. Overall, DALI is more ideal for smart lighting with smooth transitions, while 0–10 V is more suitable for basic installations.